Comparison of the original Amsler grid with the preferential hyperacuity perimeter for detecting choroidal neovascularization in age-related macular degeneration - Isaac,David Leonardo Cruvinel (2007)
PURPOSE: To compare the preferential hyperacuity perimeter (Preview PHP; Carl Zeiss Meditec, Dublin, CA) with the original Amsler grid in the detection of choroidal neovascularization (CNV) in patients with age-related macular degeneration (AMD). METHODS: Patients were classified into groups, based on the severity of the age-related macular degeneration and underwent preferential hyperacuity perimeter and Amsler grid testing. High sensitivity and or high specificity of a method were defined as the observation of at least 80% of each one the parameters. RESULTS: Sixty-five patients (65 eyes) were analyzed statistically. The sensitivity of detection of choroidal neovascularization was 70% by the Amsler grid and 90% by the preferential hyperacuity perimeter and the specificity of the Amsler grid was 85.5% and that of the preferential hyperacuity perimeter 81.8%. CONCLUSIONS: The preferential hyperacuity perimeter has greater sensitivity than the Amsler grid in the detection of choroidal neovascularization among patients over 50 years of age and is a promising method for monitoring patients with age-related macular degeneration. Although the original Amsler grid is less sensitive, it is a portable method, not expensive, accessible and presents reasonable sensitivity and high specificity in the diagnosis of choroidal neovascularization. Its use can be recommended for self-monitoring in patients with age-related macular degeneration as an alternative to preferential hyperacuity perimeter and when this method is not available.